Pharmacology and Phytochemistry of Saponin Isolated from Aloe vera for Wound Healing Activity - S. Rajput, Shailendra; K. Soni, Kapil; Saxena, R.C. (Asian Journal of Chemistry, 2010)
Aloe vera Mill. (Family-Liliaceae) water extract showed the presence of saponin with high polarity and maximum percentage yield 21.8 %. Wound healing activities were noticed within 4-8 d of granulation of wound and maximum 82.29 % maturation of collagen was observed in albino rats.